2018
DOI: 10.1038/s41467-018-04182-z
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Hexokinase-2 depletion inhibits glycolysis and induces oxidative phosphorylation in hepatocellular carcinoma and sensitizes to metformin

Abstract: In the originally published version of this Article, the colours of the bars in Fig. 4b were inadvertently switched during the production process, such that 'HK2-Dox' and 'HK2+Dox' were depicted in red and 'Nt-Dox' and 'Nt+Dox' were depicted in blue. These errors have now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Accordingly, the drug combination reduced the expression of HK2, PFKP, and MCT4 in HepG2 cells, and significantly decreased the ECAR under both normoxia and hypoxia/CoCl 2 treatment, even though no further enhancements were promoted in comparison with single treatments. The relevance of targeting these genes finds support in previous studies demonstrating their key role in HCC tumor growth (44,75,76).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Accordingly, the drug combination reduced the expression of HK2, PFKP, and MCT4 in HepG2 cells, and significantly decreased the ECAR under both normoxia and hypoxia/CoCl 2 treatment, even though no further enhancements were promoted in comparison with single treatments. The relevance of targeting these genes finds support in previous studies demonstrating their key role in HCC tumor growth (44,75,76).…”
Section: Discussionmentioning
confidence: 67%
“…Under normoxic conditions, both palbociclib and regorafenib as well as their combination down-regulated the expression of hexokinase 2 (HK2), the major HK isoform expressed in HCC (44), and phosphofructokinase platelet (PFKP), a major isoform of PFK-1 controlling the first rate-limiting step of glycolysis in cancer cells (45) (Figure 7C). Under hypoxic conditions, both genes were significantly down-regulated by regorafenib and no further decrease was induced by the combination.…”
Section: Effects Of the Simultaneous Combination Of Palbociclib With mentioning
confidence: 99%
“…Hexokinases are enzymes that phosphorylate glucose to produce glucose-6-phosphate, which is the first step in most glucose pathways, including glycolysis. Hexokinase 2 (HK2) is the major isoform that is overexpressed in cancers (218) and its depletion can ameliorate the outcomes in a model of hepatocellular carcinoma (219). There are some indications that, under hypoxic conditions, the overexpression of HK2 can facilitate EMT (220).…”
Section: Glycolysismentioning
confidence: 99%
“…In contrast, the pyruvate dehydrogenase levels was higher in SEMA3F KD groups, but Pyruvate kinase isozymes M2(PKM2) expression levels was not difference between two groups. These results suggested that level of aerobic glycolysis of LECs in SEMA3F KD groups was lower than that in control groups in hypoxia, it converted glycolysis to the Krebs cycle was not be blocked(Liu et al ,2017;DeWaal et al ,2018; Sukonina et al ,2019). To further determination the efficacy to knock down SEMA3F of CRCs inhibition glycolysis of hLECs in hypoxia, therefore, we use 3-bromopyruvate to inhibit the glycolysis of the two groups.…”
Section: Resultsmentioning
confidence: 83%